From the Leader’s Values to Organizational Values: Toward a Dynamic and Experimental View on Value Work in SMEs - Ludivine Adla; Marie Eyquem-Renault; Virginie Gallego-Roquelaure (M@n@gement, 2020)
In this article, we contribute to empirically account for Selznick’s argument about the moral competence of organizations by showing the ways an organization collectively thinks, acts, feels and expresses needs (Callon, 2006) related to its desirable ends. These are related to the socio-technical arrangements processing the values work. Made up of devices, actors, and social groups, the socio-technical arrangements are brought into existence by means of material embodiments of values in artifacts. Considering the case of a leader who has founded a firm in the social and solidarity sector in order to implement his personal values, we contribute to better understanding value-based leadership. We trace how this leader’s values are progressively and collectively materialized into artifacts that create new relationships in which the organization’s desirable ends are to be met. Adopting a relational and processual view on values work, we trace the evolution of this socio-technical arrangement to maintain or restore the implementation of organizational values in an evolving context, contributing to a dynamic view on organizational values.